Besonderes Verwaltungsrecht - Huber, Peter Michael (De Gruyter, 2011)
The book's objective is to provide an easy-to-read, systematically arranged scientifically practical textbook. In addition to students, it also serves judges, lawyers and civil servants as a valuable aid, which offers accuracy and clarity despite the abundance of subject material. The law card catalogue is added as CD-ROM in the current 2005 version: it includes almost 5000 comments on rulings from the areas of civil law, public law and criminal law. The quoted rulings in the book each contain a note corresponding to where they can be found in the law card catalogue
Description based upon print version of record
Keywords: Electronic books; Lehrbuch; Entscheidungssammlung; Besonderes Verwaltungsrecht; Deutschland